Perancangan Produk Furnitur Hemat Ruang dan Booth dengan Pendekatan Modular Desain oleh Vidi Vici Collection - Prijono, Vincent Tan; Purwoko, Gervasius Herry (Universitas Ciputra Surabaya, 2024)
The increasing population of Indonesian people has also increased the demand for household products, especially furniture, to meet their needs. However, the condition of a small residence makes the space appear cramped and full. VIDI VICI is an online-based furniture manufacturing company with a mass market share, which refers to providing various large-scale furniture and interior accessory needs. The company carries modular concept furniture products with a minimalist style that divides the system into smaller parts called modules, which can be modified, replaced, and created independently with other modules. The modular approach allows for flexibility and adaptability in furniture products, which can be adapted to various needs and space conditions. The design concept for this interior product is in the form of space-saving furniture or interior products such as space-saving furniture and booths. The module is designed to be compatible with other modules, using the system stack lock provides freedom in adjusting the position of the product according to needs and desires without fear of it shifting or falling. At the same time, the booth carries a minimalist style modular concept with a simple, plain, and open layout. The method used in this design has 5 stages, including observation, survey, and literature study, the initial sketch process and 3D stage, the development of the initial sketch into a design, and the design testing stage. Implementing modular designs in furniture and booth products is expected to provide added value for users, especially regarding flexibility and space efficiency.